Sustained censorship in TR (2026-05) (Turkey) - Voidly (Voidly Global Censorship Index, 2026)
WARNING severity censorship detected in Turkey. Data sourced from OONI.
Censorship Incident ID: TR-2026-0135. Severity: warning. Confidence: 70%